2016
DOI: 10.1590/0102-311x00118215
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da cascata de cuidado na prevenção da transmissão vertical do HIV no Brasil

Abstract: Cad. Saúde Pública, Rio de Janeiro, 32(9):e00118215, set, 2016Avaliação da cascata de cuidado na prevenção da transmissão vertical do HIV no Brasil Evaluation of the cascade of care in prevention of mother-to-child HIV transmission in Brazil Evaluación de la cascada de cuidado en la prevención de la transmisión vertical del VIH en Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
1
14
1
22
Order By: Relevance
“…It is estimated that, in Brazil, 98.7% of pregnant women receive prenatal care [ 23 ]. In this study, 95.8% of pregnant women with HIV had at least one prenatal care appointment, a value higher than that observed by Miranda et al [ 24 ] in a study that evaluated women who were recorded in the SINAN “HIV in pregnancy”, where the coverage ranged from 79% to 91%.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It is estimated that, in Brazil, 98.7% of pregnant women receive prenatal care [ 23 ]. In this study, 95.8% of pregnant women with HIV had at least one prenatal care appointment, a value higher than that observed by Miranda et al [ 24 ] in a study that evaluated women who were recorded in the SINAN “HIV in pregnancy”, where the coverage ranged from 79% to 91%.…”
Section: Discussioncontrasting
confidence: 55%
“…A study carried out with pregnant women documented in SINAN “HIV in pregnancy” [ 24 ] identified missed opportunities of HIV-MTCT prevention in all five regions of the country, but with higher frequency in the North and Northeast regions. Less missed opportunities were observed in women diagnosed with pre-gestational infection and higher in those who did not receive a diagnosis of HIV during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Upon accepting, men understood it would be a normal pregnancy, as they would need care to prevent the transmission of HIV to their child. In a study that evaluated the cascade of care for the reduction of vertical transmission of HIV in six Brazilian states, failures were identified in all healthcare points, as well as the need for a connection between referral and primary care services, focusing on family care (22) . Action planning in health services also involves establishing bonds and trust between users and professionals with the aim to minimize the dimensions related to prejudice and stigma that are still present in this relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluating the data from HIV-infected pregnant women and children in five states and the Federal District, Miranda et al have shown that the best source to find children under 13 years of age with HIV was the SISCEL; SINAN contained less than a third of the cases 10 .…”
Section: Discussionmentioning
confidence: 99%